PENGARUH KEMAMPUAN NUMERASI DALAM MENYELESAIKAN MASALAH MATEMATIKA TERHADAP PRESTASI BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA STKIP PARIS BARANTAI - evi novianty & Hartini (STKIP Paris Barantai, 2025)
This study aims to determine the relationship between numeracy skills and achievement in learning mathematics as indicated by the Grade Point Average (GPA).The sample in this study were 30 students of the Mathematics Education study program at the Paris Barantai High School Of Teaching And Science Education.The type of research used is a quantitative method with ex post facto research techniques.Data analysis in this study used descriptive statistics and inferential statistics with Spearman correlation analysis. This study uses one independent variable, namely numeracy ability and one dependent variable, namely learning achievement.The results of this study indicate that numeracy has a positive and significant effect on student learning achievement with a 95% confidence level and a sig. confidence level and a sig. value of 0.009 < 0.05 and balue of the correlation coefficient rxy = 0.476. which is in the moderate or strong enough category. The contribution of numeracy in influencing the level of learning achiecment is 22.65 %.While the rest is influenced by other factors. Thus, the result of this study indicate that if the numeracy ability of each mathematics education student is high,the learning achievement that will be obtained is also high